Genotoxicity of Anesthetics Evaluated In Vivo (Animals). (24th June 2015) - Braz, Mariana G.; Karahalil, Bensu
Abstract : The anesthesia has been improved all over the years. However, it can have impact on health, in both patients and animals anesthetized, as well as professionals exposed to inhaled anesthetics. There is continuing effort to understand the possible effects of anesthetics at molecular levels. Knowing the effects of anesthetic agents on genetic material could be a valuable basic support to better understand the possible mechanisms of these agents. Thus, the purpose of this review is to provide an overview on the genotoxic potential, evaluated in animal models, of many anesthetics that have already been used and those currently used in anesthesia.